4CPS-230 Prospective study to explore the impact of a clinical pharmacist in a cardiac surgical population or after acute coronary syndrome. (2nd March 2018) - Braibant, M; Larock, AS; Dive, A; Horlait, G; Bulpa, P; Michaux, I; Hecq, JD; Krug, B; Spinewine, A
Abstract : Background: Patients in the intensive care unit (ICU) are at risk of medication errors (polypharmacy, critical nature of their illnesses and use of high-risk drugs). Collaboration with a clinical pharmacist can be helpful in minimising these risks. In order to develop and sustain clinical pharmacy activity in the ICU at our hospital, formal evaluation of the potential benefit was required. Purpose: To describe the characteristics of interventions performed by an ICU clinical pharmacist, including their clinical relevance and likelihood of preventing adverse drug events (ADEs), as well as carrying out a cost analysis on a subgroup of critical interventions. Material and methods: A prospective interventional study was conducted in the cardiac and cardio-surgical ICU of a university teaching hospital. The clinical pharmacist provided pharmaceutical care to cardiovascular surgical and acute coronary syndrome ICU patients over a 9 week period. All clinical pharmacy interventions (CPIs) were recorded and evaluated by two independent evaluators for clinical relevance and likelihood of preventing ADEs. The CPIs were categorised in a risk classification system adapted from the Society of Hospital Pharmacists of Australia. For the cost analysis, we relied on German adverse drug events micro-costing data by Rottenkolber et al. Results: A total of 230 CPIs were performed in 58 patients. The acceptance rate was 85.5%. The medication classes most frequently involved were: blood and coagulation (16.9%), cardiovascular system (14.8%), pain and fever drugs (14.8%). Sixty-six (33.8%) interventions were considered high/extreme risk, and anticoagulants and antiplatelet agents alone accounted for 25.8% of those. The cut-off to cover the salary of the clinical pharmacist could be reached, if 24 severe adverse events on anticoagulants and antiplatelet agents were avoided per 7 weeks. Two-thirds of all CPIs required the presence of the pharmacist in the unit. Analysis of the medical record (45.1%) and contact with a primary care provider (46.7%) were proportionally the sources of information most often used in the case of high/extreme CPIs. Conclusion: This study provides data that supports the expansion of clinical pharmacy services to cardiovascular surgical patients in the ICU. Reference and/or Acknowledgements: 1. Rottenkolber D, et al. Costs of adverse drug events in German hospitals – a microcosting study. Value Health2012Sep–Oct;15(6):868–875. No conflict of interest